2021
DOI: 10.1111/1752-1688.12968
|View full text |Cite
|
Sign up to set email alerts
|

An Open‐Source Web Application for Regional Analysis of GRACE Groundwater Data and Engaging Stakeholders in Groundwater Management

Abstract: Since 2002, National Aeronautics and Space Administration’s Gravity Recovery and Climate Experiment (GRACE) allows scientists of various disciplines to analyze and map changes in total water storage globally. Although the raw data are available to the public, the process of viewing, manipulating, and analyzing GRACE data can be difficult for those without strong technological backgrounds in programming or geospatial software. This is particularly true for water managers in developing countries, where GRACE dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Furthermore, we conducted a temporal and geospatial assessment to monitor changes in groundwater in the cocoa-growing regions of Ghana, by leveraging the Gravity Recovery and Climate Experiment (GRACE) and the Global Land Data Assimilation System (GLDAS) dataset provided by the GRACE Groundwater Subsetting tool (GGST) 37 under the NASA SERVIR program’s API and Google Colab Notebook. The Groundwater storage anomaly in the database is derived using the mass balance approach (Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we conducted a temporal and geospatial assessment to monitor changes in groundwater in the cocoa-growing regions of Ghana, by leveraging the Gravity Recovery and Climate Experiment (GRACE) and the Global Land Data Assimilation System (GLDAS) dataset provided by the GRACE Groundwater Subsetting tool (GGST) 37 under the NASA SERVIR program’s API and Google Colab Notebook. The Groundwater storage anomaly in the database is derived using the mass balance approach (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, long-term monthly mean anomaly spatial plots were created to visualize the spatial and seasonal variability of groundwater as well as the mass balance components in the cocoa-growing regions in Ghana. Note that the gaps in the GRACE total water storage anomaly (TWSa) were imputed based on the methods described in 37 , 38 and the snow water equivalent is zero for the region.…”
Section: Methodsmentioning
confidence: 99%
“…An overview of the Tethys Platform and links to documentation, bug reporting, and support forum are available online at http://www.tethysplatform.org. The Tethys platform has created a common medium for scholars and scientists enabling them to envision, develop, and deploy several notable Earth Observation web applications (McStraw et al;McDonald et al, 2019;Nelson et al, 2019;Qiao et al, 2019;Saah et al, 2019;Gan et al, 2020;Bustamante et al, 2021;Khattar et al, 2021;Sanchez Lozano et al, 2021). The application structure for the NASAaccess Tethys web application uses the Model-View-Controller (MVC) software architecture discussed in McDonald et al, (2019).…”
Section: Tethys Application Frameworkmentioning
confidence: 99%
“…GRACE data have been used for various applications, such as flood studies [25][26][27][28][29], drought studies [30][31][32][33][34][35], and general hydrologic investigations focusing on regional water storage and trends [36][37][38]. Recent research has demonstrated the use of GRACE data for monitoring variations in groundwater storage [39][40][41][42][43] including variations in groundwater depletion in arid and semiarid regions [15,44,45]. GRACE data have proven valuable in monitoring global water storage changes [46].…”
Section: Grace Datamentioning
confidence: 99%